THE INFLUENCE OF WHATSAPP GROUP-BASED BLENDED LEARNING ON STUDENTS' CRITICAL THINKING ABILITIES - Herlina, Meti; Lubis, Rukiah; Fitriyani, Nesti (BioCONCETTA, 2023)
This research aims to determine the influence of WhatsApp Group-based Blended Learning on students' critical thinking abilities. The study adopts a quasi-experimental design and is conducted at SMAN 8 Seluma. The sample consists of Class XII MIPA 1 as the experimental group receiving blended learning treatment, and Class XII MIPA 2 as the control group undergoing conventional learning. The Statistics Group Pretest-Posttest design is employed. Non-Probability Sampling is used for sample selection, and data analysis is performed using the t-test. The research findings reveal a significant difference in students' critical thinking abilities between the experimental and control groups. The average critical thinking ability score for the experimental group is 49.55, while for the control group, it is 46.43. The t-test results indicate a significance level of Sig. (2-tailed) = 0.000 < 0.05, and Tcount (calculated t-value) = 5.668 > Ttable (critical t-value) = 2.022 (sig: 5.668 > 2.022). Therefore, H1 is accepted, and H0 is rejected, leading to the conclusion that WhatsApp Group-based Blended Learning has a significant influence on students' critical thinking abilities.